IMPLEMENTASI UNDANG-UNDANG SISTEM PERADILAN PIDANA ANAK DALAM PENGGUNAAN UPAYA PAKSA TINDAK PIDANA NARKOTIKA OLEH KEPOLISIAN RESOR KOTA PEKANBARU - Astuty, Deny; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is a country where narcotics crime is an extraordinary crime, that can affect the life of the nation which became the successor state of the nation and future goals. Narcotics crime is not looking at anyone who commits this crime, minors can become the subjects and the victims of this narcotics crime. Narcotic crime is unconventional form of crime that conducted systematically, using a great modus operandi with advanced technology and done in a well organized. The eradication of criminal acts of narcotics required performance of the police which originated from the stage of the investigation to law enforcement in the form of force efforts against minors.Accordance with the above description, the writer is interested to do research with the title Implementation of Act Criminal Justice System of Children in Use for Force Attempts of Crime by Police Resort of Pekanbaru. The writing of this thesis aims to know, First the implementation of act criminal justice system of children in the use of force efforts by police resort of Pekanbaru. Second, to find out what becoming obstacles in implementation of act criminal justice system of children in the use of force efforts by police resort of Pekanbaru. Third, to find out the efforts for overcome the obstacles in implementation of act criminal justice system of children in the use of force efforts by police resort of Pekanbaru.The writing of this thesis, the writer uses the methods of sociological research . The sociological research is research done by identifying the law and how the effectiveness of the law prevailing in society. The nature of research is descriptive, tha give an overview in detail about implementation of act criminal justice system of children in the use of force efforts by police resort of Pekanbaru. giving a clear and detailed picture of the implementation of Law Criminal Justice System Children in Forced Efforts Using Narcotics Crime. The results of research carried out qualitative analysis and using deductive method, namely the problem of decomposition which are common to a certain case.From the results it can be concluded that in implementation of force effort narcotics crime commited by minors still in hesitance, especially in the form forceful measures of arrest, therefore the writer suggest to do revision to Act criminal justice system of children and Act Narcotics to make it more clear in terms of the law enforcement by investigator.Keywords: Minor Investigations - Narcotics Crime - Law Enforcement.